(untitled) (Ciudades, 2017)
Urban Planning in East Berlin before 1989 is often referred as lack of interest. Even a singular project as the rebuilding of the Nikolaiviertel is often ignored, if not trivially considered, probably due to its neohistorical architectural language as much as its becoming an outstanding tourist centre in the recent years. This is more significant if we look at the attention paid to other projects after the reunification. This text tries to vindicate some lessons in this project, as we see it as an enquiry on urban methods for creating urban complexity and understanding the city as an historical object in evolution. If possibly trivial as a project, it is not at all as a process.